Amelia Bedelia joins the club - Parish, Herman (I can read!, 1 Beginning reading, 2014)
"Amelia Bedelia loves her school. Her whole class gets along--except when it rains. Then they split into two groups--the Puddle Jumpers and the Puddle Stompers. Both clubs ask Amelia Bedelia to join, but she doesn't want to choose between her friends. Luckily, Amelia Bedelia finds a solution that makes a big splash with everyone"--